Perancangan Sistem Pembangkit Listrik Biomassa Sawit (PLTBS) Kapasitas 5 MW - Ari Wibowo (Jurnal Mekanika dan Sistem Termal, 2016)
Based on 2014 PLN statistic data, Riau and Riau Island Region peak load reached 261.02 MW, while installed power plant capacity of 166.62 MW capable power only 98.70 MW. This causes frequent rolling blackouts in the Riau city and its surrounding. On the other hand, Riau has huge renewable energy sources derived from oil palm industry. Palm Oil Mill (POM) are scattered throughout the region of Riau, where the plant produces biomass waste called empty fruit bunch (EFB), shell and fiber. These biomass waste especially EFB has very huge potency tobe converted to energy. The purpose of this study is to mapping the potencies of electrical energy generated from the biomass waste produced by two palm oil mills of PTPN V. Lubuk dalam POM and Sei Buatan POM has a very good performance over the last five year, with FFB processed an average over 200.000 ton/year. Biomass samples, then tested in the laboratory to obtain the calorific value. The expected electric power generated then analyzed based on the production data and the caloric value of the biomass waste. The calculation resulting 5 MWh electric power can be generated, with only use EFB from both POM as fuel feedstock of the boiler. The biomass power plant based on Rankine Cycle System. Four main equipment in the Rankine cycle, boiler, turbine-generator, condenser and pump, then calculated based on the power generated and availability of feedstock. The biomass power plant system designed with superheated steam with its pressure and temperature of 32 barg 400oC.